Birth, stillbirth and death registration data completeness, quality and utility in population-based surveys: EN-INDEPTH study - Simon Kasasa; Davis Natukwatsa; Edward Galiwango; Tryphena Nareeba; Collins Gyezaho; Ane Baerent Fisker; Mezgebu Yitayal Mengistu; Francis Dzabeng; M. Moinuddin Haider; Judith Yargawa; Joseph Akuze; Angela Baschieri; et al. (BMC, 2021)
Abstract Background Birth registration is a child's first right. Registration of live births, stillbirths and deaths is foundational for national planning. Completeness of birth registration for live births in low- and middle-income countries is measured through population-based surveys which do not currently include completeness of stillbirth or death registration. Methods The EN-INDEPTH population-based survey of women of reproductive age was undertaken in five Health and Demographic Surveillance System sites in Bangladesh, Ethiopia, Ghana, Guinea-Bissau and Uganda (2017-2018). In four African sites, we included new/modified questions regarding registration for 1177 stillbirths and 11,881 livebirths (1333 neonatal deaths and 10,548 surviving the neonatal period). Questions were evaluated for completeness of responses, data quality, time to administer and estimates of registration completeness using descriptive statistics. Timing of birth registration, factors associated with non-registration and reported barriers were assessed using descriptive statistics and logistic regression. Results Almost all women, irrespective of their baby's survival, responded to registration questions, taking an average of < 1 min. Reported completeness of birth registration was 30.7% (6.1-53.5%) for babies surviving the neonatal period, compared to 1.7% for neonatal deaths (0.4-5.7%). Women were able to report age at birth registration for 93.6% of babies. Non-registration of babies surviving the neonatal period was significantly higher for home-born children (aOR 1.43 (95% CI 1.27-1.60)) and in Dabat (Ethiopia) (aOR 4.11 (95% CI 3.37-5.01)). Other socio-demographic factors associated with non-registration included younger age of mother, more prior births, little or no education, and lower socio-economic status. Neonatal death registration questions were feasible (100% women responded; only 1% did not know), revealing extremely low completeness with only 1.2% of neonatal deaths reported as registered. Despite > 70% of stillbirths occurring in facilities, only 2.5% were reported as registered. Conclusions Questions on birth, stillbirth and death registration were feasible in a household survey. Completeness of birth registration is low in all four sites, but stillbirth and neonatal death registration was very low. Closing the registration gap amongst facility births could increase registration of both livebirths and facility deaths, including stillbirths, but will require co-ordination between civil registration systems and the often over-stretched health sector. Investment and innovation is required to capture birth and especially deaths in both facility and community systems.